IMPROVING STUDENTS VOCABULARY MASTERY BY USING PICTURES MEDIA AT THE THIRD GRADE OF SDN 010 KEPENUHAN - Marzuki, Heri (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This Research was classroom action research (CAR), this research was conducted in two cycles that consisted of four meeting in a cycle. This research was conducted to overcome the existing problem on the field as well as to described and also explain whether the pictures media could improve the studentsâ vocabulary mastery. The result of this research in pre-test 56.80%, cycle 1 71.80% and cycle 2 80.47%. The result of this research indicated that the pictures media could improve the studentsâ vocabulary mastery, then found the factors that improved: (1) The selection of appropriated pictures media. (2) Applying pictures media. (3) Management of the class. (4) Practiced. (5) Teacher supported the students as the facilitator and motivator